Analysis of Lecturer Readiness Assessment Standards for Semester III PBA Students at UIN Sunan Kalijaga In Implementing The Independent Curriculum - Tolibuddin Siregar; Zainal Arifin Ahmad; Zamakhsari Zamakhsari; Muhajir Muhajir (Edumaspul: Jurnal Pendidikan, 2024)
The UIN Sunan Kalijaga Yogyakarta Campus has taken part in a series of activities towards implementing the Curriculum merdeka, namely the Independent Curriculum training in the city of Yogyakarta from 16 October to 13 November 2023. This activity was specifically carried out for the UIN Sunan Kalijaga Yogyakarta Campus. The aim of this research is to analyze teacher readiness in facing the curriculum Merdeka at the UIN Sunan Kalijaga Yogyakarta Campus. This research is a case study research (qualitative). Observation, interviews and documentation are the research methods used in this research mine. The data collection procedure is that data is collected, reduced, conclusions drawn, and tested using angulation. The research results show that: 1) Only a small number of lecturers as a worksheet (Lk) for CP, TP, ATP, and others and teaching modules. But it's not finished yet. 2) The lecturer has not prepared the learning project module, only prepared a worksheet (LK) for students to fill in. 3) For all courses taught in class C, facilities in the form of teaching materials (books) have been provided by the madrasah. Additional facilities in the form of ebooks and other teaching materials are owned and prepared by each lecturer in the Arabic language learning planning course. 4) Only some lecturers plan differentiated learning. 5) Only a small number of lecturers carry out assessments, both cognitive diagnostics and non-cognitive diagnostics. Keywords: Student Readiness, Implementation of the Independent Learning Curriculum, UIN Sunan Kalijaga Yogyakarta.